2007
DOI: 10.1111/j.1651-2227.2007.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of severely malnourished under‐five children hospitalized with diarrhoea, and their policy implications

Abstract: There thus is a need to incorporate appropriate, cost-effective and sustainable preventive strategies and improved management policies in the health systems as well as in social support systems in Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 15 publications
6
43
0
Order By: Relevance
“…The severely-underweight children in our study were also more likely to have illiterate or less-educated mothers (<5 years of schooling) as has been observed in previous studies in Bangladesh (9,12,(18)(19)(20)(21)(22), and the underweight children were three times more likely to have teen-aged mothers than the better-nourished children. A previous report from Kenya also showed young maternal age to be a risk factor for severe PEM (OR=3.95, p<0.001) (23).…”
Section: Discussionsupporting
confidence: 70%
“…The severely-underweight children in our study were also more likely to have illiterate or less-educated mothers (<5 years of schooling) as has been observed in previous studies in Bangladesh (9,12,(18)(19)(20)(21)(22), and the underweight children were three times more likely to have teen-aged mothers than the better-nourished children. A previous report from Kenya also showed young maternal age to be a risk factor for severe PEM (OR=3.95, p<0.001) (23).…”
Section: Discussionsupporting
confidence: 70%
“…The prevalence of stunting and underweight in the present study was higher than in Pakistani children (35% stunting and 29.5% underweight) (Mian et al 2002) and Malaysian children (29.2% stunting and 26.1% underweight) (Marjan et al 1998) but stunting was lower than in Indonesian children (55% stunting) (Hadju et al 1995). Severe stunting and underweight (below (3 Z-score) of the present study was comparable to Bangladeshi children (11% stunting and 16% underweight) (Chisti et al 2007). Frongillo et al (1997) analysed the socio-economic factors that were responsible for undernutrition (100) in different countries, and also indicated that greater prevalence of undernutrition in Asians nations was due to environmental factors and ethnic differences.…”
Section: Discussionmentioning
confidence: 54%
“…Simultaneous changes have also been observed in the risk factors for malnutrition (2,15,16) . We found a high baseline prevalence for stunting and underweight in Dhaka, which might be due to the longer period of observation in Dhaka (20 years, 1993-2012) as compared with Matlab (13 years, 2000-2012).…”
Section: Discussionmentioning
confidence: 94%